John Banville’s "Shroud": A deconstructionist’s confession - Kucała, Bożena (Adam Mickiewicz University, 2013)
This article analyses John Banville’s novel Shroud as the protagonist’s autobiography which both follows and resists the confessional mode. Axel Vander, an ageing famous academic and champion of deconstruction, faces the necessity to confront his real self, although he spent his entire academic life contesting the concept of authentic selfhood. Alluding to the infamous case of Paul de Man, whose deconstructionist theories have been reinterpreted in the light of the revelation of his disgraceful wartime past, Banville’s novel presents a man who veers between the temptation to fall back on his theories in order to uphold a lifelong deception, and the impulse to reveal the truth and achieve belated absolution. The article examines Vander’s narrative as an attempt at a truthful account of his life, combined with the conflicting tendency to resist self-exposure. Despite the protagonist’s ambivalent and selfcontradictory motivations, his account of his life belongs to the category of confessional writing, with its accompanying religious connotations. It is argued that the protagonist’s public denial of authentic selfhood is linked to his private evasion of moral culpability.
Keywords: John Banville; Paul de Man; deconstruction; autobiography; confession